Age Grades, Indigenous Socialisation and Sustainable Development in Igala Communities - UGBOJA, Anthony; DADA, Dare Babatunde (Àgídìgbo: ABUAD Journal of the Humanities, 2025)
This paper is focused on age grade system as agent of indigenous socialization and sustainable development in Igala communities. The paper examines the roles of age grades as agents of indigenous socialization and sustainable development in Nigeria. It investigates the cultural influence of Anambra West of the South East, Nigeria and Ibaji, Local Government Area of Igala Extraction as a result of proximity. The problem of the study is seeking solutions to the problems of youths restiveness, which is very prevalent in the society today in other to achieve SDGs goal by 2030. The study relies on both primary and secondary sources to justify the arguments on the role of age grade. Oral interview was conducted and the results as seen in the table show that age grade system helps, in improving socio -cultural, sociological and philosophical/ ideology of communities,by expanding the synergy of various members and mobilizing them for socialization in different forms for sustainable development goal. The paper recommends among others that: government should use age grade as platform for socialization in most programs in rural communities since there is already an established modus operandi to implement indigenous curriculum.